Um estudo psicanalítico sobre a escrita autobiográfica de dois autores autistas: Daniel Tammet e Naoki Higashida - Correia, Rosângela de Faria (2023)
The objective of this research is to reflect on the autobiographical and poetic writing produced by autistic subjects whereby they report their particular experiences and ways of being in the world. They especially describe the difficulties encountered in language acquisition and in voice appropriation. The focus of the study comes from the reading of two autobiographical works, initially ties Daniel Tammet's work “Born on a Blue Day” (2007) will be highlighted. He is a high-functioning autistic with great mathematical skills and considerable language learning capability. The author describes his autistic characteristic, his thoughts based on images, his interest in numbers and the particular relationship with language. Later the book “What makes me jump” (2014) by Naoki Higashida, a teenager who reveals his emotions, feelings and his world permeated with sensitivity and poetry. The author narrates experiences of suffering and anguish for not being able to communicate with people. Naoki is a boy who does not speak, but it is through writing that he can transmit his singularity and the way he found to establish social. This study has as its theoretical and clinical foundation in the lacanian psychoanalysis and seeks to give focus on the fact that these productions broaden and expand the understanding of autisms. The autobiographical writings reveal their own knowledge, and thus contribute to the psychoanalytic clinic, and have important implications in the social field